Implementation of Web-Based File Sharing Security System - Yuliana, Mike; Hidayah, Nuril; Sudarsono, Amang (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2024)
File-sharing activities become a bridge for communication in the form of data between one party and another party. File sharing allows users to share data with other users, by uploading data to the server computer and other users can download data from the server computer. A document security system is indispensable to keep document data safe until its destination. File Web Sharing will transmit data with cryptographic methodologies. The algorithm used is Advanced Encryption Standard (AES), Data Encryption Standard (DES), and Blowfish. This study aims to compare the performance of AES, DES, and Blowfish algorithms when implemented to secure file sharing. Performance research results show that the DES algorithm is on average 8.35% faster than AES and the Blowfish algorithm is 7.11% faster than AES. Memory usage capacity testing shows that the AES algorithm requires 4.82% greater memory capacity than Blowfish, and the DES requires 2.41% greater memory capacity than the Blowfish algorithm. Kegiatan file sharing menjadi jembatan komunikasi data antara satu pihak dengan pihak lainnya. File sharing memberikan pengguna kemampuan untuk berbagi data dengan pengguna lain, dengan cara mengunggah data ke komputer server dan pengguna lain dapat mengunduh data dari komputer server. Sistem keamanan terhadap dokumen sangat diperlukan untuk menjaga data dokumen tetap aman sampai tujuannya. Web File Sharing akan mengirimkan data dengan metodologi kriptografi. Algoritma yang digunakan adalah Advanced Encryption Standard (AES), Data Encryption Standard (DES), dan Blowfish. Penelitian ini bertujuan untuk membandingkan kinerja algoritma AES, DES dan Blowfish saat diimplementasikan untuk mengamankan file sharing. Hasil pengujian kinerja menunjukkan bahwa algoritma DES rata-rata 8,35% lebih cepat dibandingkan AES sedangkan Blowfish 7,11% lebih cepat dibandingkan AES. Berdasarkan pengujian kapasitas penggunaan memori terlihat bahwa AES membutuhkan kapasitas memori 4,82% lebih besar dibandingkan Blowfish dan DES membutuhkan kapasitas memori 2,41% lebih besar dari Blowfish.